2019
DOI: 10.1111/febs.15012
|View full text |Cite
|
Sign up to set email alerts
|

Complex genetic interactions between DNA polymerase β and the NHEJ ligase

Abstract: Mammalian cells possess multiple pathways for repairing various types of DNA damage. Although the molecular mechanisms of each DNA repair pathway have been analyzed by biochemical analysis and cell biological analysis, interplay between different pathways has not been fully elucidated. In this study, using human Nalm‐6–mutant cell lines, we analyzed the relationship between the base excision repair factor DNA polymerase β (POLβ) and DNA ligase IV (LIG4), which is essential for DNA double‐strand break (DSB) rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 44 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The alkylating agent, MMS, alkylates guanine and adenine to 7-methylguanine and 3-methyladenine, respectively [26]. Further, the alkylated base is repaired via base excision repair (BER), and in our previous study, we reported that accumulated base damage not repaired by BER is converted to DSBs in BER-proficient Nalm-6 cells and that at least some DSBs are repaired by NHEJ [18,21]. One-ended DSBs also occur in MMS-treated human A549 cells [27].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The alkylating agent, MMS, alkylates guanine and adenine to 7-methylguanine and 3-methyladenine, respectively [26]. Further, the alkylated base is repaired via base excision repair (BER), and in our previous study, we reported that accumulated base damage not repaired by BER is converted to DSBs in BER-proficient Nalm-6 cells and that at least some DSBs are repaired by NHEJ [18,21]. One-ended DSBs also occur in MMS-treated human A549 cells [27].…”
Section: Resultsmentioning
confidence: 99%
“…The human pre-B cell line, Nalm-6, and its derivative were cultured in a 5% CO 2 incubator at 37 • C in minimum essential medium (MEM; Nissui Seiyaku, Tokyo, Japan) supplemented with 10% heat-inactivated fetal bovine serum (GE Healthcare, Marlborough, MA, USA), 2 mM MEM non-essential amino acids (Wako Pure Chemical, Osaka, Japan), 1 mM sodium pyruvate (Wako Pure Chemical), 50 µM 2-mercaptoethanol (Wako Pure Chemical), and 0.15 mM vitamin B12 (Sigma-Aldrich, St. Louis, MO, USA) [21]. The human cervical cancer cell line, HeLa, was obtained from the RIKEN Bioresource Research Center and cultured in a 5%-CO 2 incubator at 37 • C in Dulbecco's modified Eagle's medium (Sigma-Aldrich) supplemented with 10% heat-inactivated fetal bovine serum (GE Healthcare) and 100 U/mL of penicillin/streptomycin (Wako Pure Chemical).…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…However, many details are still unknown ( 69 ). For example, leukemia cells lacking DNA pol β cannot perform the BER pathway efficiently but can activate the NHEJ pathway to repair damage by alkylation ( 70 ).…”
Section: Tumor Cells Activate Signaling Pathways Involved In Dna-damage Response To Survive Ionizing Radiationmentioning
confidence: 99%